Model of accreditation caceleration for international reputable journals - Helvi Yanfika; Novita Nurdiana (Open Global Scientific Journal, 2023)
Scientific journals serve as benchmarks for academic achievement, aiding researchers in publishing their work and assisting others in locating high-quality sources. Enhancing accreditation is crucial for elevating the competitiveness of the University of Lampung, not only on a national but also an international scale. This is integral to realizing the vision of the University of Lampung, set to become one of the Ten Best Universities in Indonesia by 2025. Therefore, a journal acceleration model is needed to support journals at the University of Lampung to become journals with global reputation. The objective of this research is to develop a model for journal acceleration policy. The methodology employed to establish the acceleration model for this journal is a SWOT analysis, a strategic planning method utilized to assess the strengths, weaknesses, opportunities, and threats within the institution (University of Lampung). This assessment is conducted through Focus Group Discussion (FGD) activities, employing Participatory Rural Appraisal (PRA) techniques, and in-depth interviews. The results of the study of the accelerated accreditation model for journals with global reputation with the SWOT strategy in S-O collaboration (Strengths and Opportunities), namely collaborating with international institutions to send and share articles, coaching for preparing Scopus documents from editors who are experienced in managing global reputations, increasing the internationalization of local journals under the University of Lampung. Furthermore, it highlights initiatives to promote collaboration among writers across countries, leveraging available facilities and conveniences to foster the development of international journals.